American Muslim Women, Religious Authority, and Activism: More Than a Prayer By Juliane Hammer (Austin: The University of Texas Press, 2012. 271 pages.) (American Journal of Islam and Society, 2014)
In American Muslim Women, Religious Authority, and Activism: More Than aPrayer, Juliane Hammer traces recent conversations around gender and religionwithin American Muslim communities. Taking as a starting point the mixedgenderFriday prayer led by Amina Wadud in 2005, the author examines howquestions of gendered religious authority have been negotiated through interpretationsof scripture and religious laws, challenges to constructions of traditionand community, contestations surrounding prayer spaces, and representationsof Muslim women in the media and autobiographical narratives.100 The American Journal of Islamic Social Sciences 31:1The result is a valuable and insightful mapping of some of the majorscholars, activists, and public figures engaged in work related to women, gender,and Islam in North America. Based on an analysis of texts produced byfemale American Muslim scholars and writers since the 1980s and especiallywithin the past decade, the book highlights women’s contributions to debatesaround women-led prayer, Qur’anic interpretations, women’s spaces inmosques, and women’s leadership within Muslim communities, among otherissues. Hammer acknowledges that of many of the texts she studies have a“progressive” leaning, but frames this as itself a research finding that reflectsthe perspectives and voices most likely to be published or otherwise highlightedwithin an American context ...